DIGITALIZATION AND THE DILEMMA OF IMPLEMENTING SAK EMKM: A PHENOMENOLOGICAL STUDY OF COGNITIVE AND SOCIO-TECHNICAL BARRIERS IN MULTISECTOR MSMES IN SERANG CITY - Faishal Rachman Wahid; Masiyah Kholmi (RADJA PUBLIKA, 2025)
This qualitative phenomenological study examines the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in eight multi-sector MSMEs in Serang City. Through in-depth interviews, participant observation, and document analysis during March-August 2024, it was found that cognitive barriers (misinterpretation of accounting terminology, perceived administrative burden) were the dominant factors hindering the adoption of SAK EMKM. Technical barriers were sector-specific: culinary businesses faced inaccurate recording of daily cash transactions, while photography services businesses experienced difficulties classifying retainer income. This study proposes a